Soy and oats as ingredients for non-dairy products - Salovaara, Hannu (MTT, 2004)
The market for dairy alternatives represents a rapidly growing sector supported by an increased awareness of milk allergy and by a trend towards a vegetarian lifestyle. Soy dairy alternatives in particular have been expanding. However, recently oat-based products have been developed and are challenging the role of soy-based foods as alternatives to dairy milk and yoghurts. Soy and oats both have nutritional benefits as food ingredients. Soy has a high content of protein of high nutritional value, and oats are known as a good source of gel-forming dietary fibre. Both can carry an FDA-approved health claim may reduce the risk of heart disease in the USA. Amounts justifying the health claim are 6.25 g and 0.75 g of soy protein and of oat beta-glucan per serving, respectively. There is evidence that diets containing high amounts of soy are associated with lower incidence for certain hormone-related cancers. Proteinase inhibitors, phytic acid, plant sterols and phytoestrogens have been suggested to be responsible for the anti-carcinogenic effect. However, some individuals develop allergic reactions to soy proteins. The beany flavour of soy is rejected by many people and its removal requires costly processing. There has also been consumer concern about genetic modification, which is widely and successfully applied to soybean in the United States. Oat-based non-dairy alternatives benefit from the anecdotal reputation of oats as being less allergenic than most other foods, including other cereals. During the ten past years clinical evidence has proved oat to be harmless to celiac patients, suggesting that oats should be granted gluten-free status. The paper deals with the potential and applications of oats in the non-dairy food market making reference in particular to soy-based non-dairy foods.
Keywords: Ka; oat; soy; non-dairy